The Effect of Realistic Mathematics Approach on Mathematics Learning Outcomes of Junior High School 6 Pekanbaru - Astri Wahyuni; Yaya Sukjaya Kusumah; Surgawi Pertiwi (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2021)
The purpose of this study was to determine the effect of Realistic Mathematics Approach on the learning outcomes of seventh grade students of Junior High School 6 Pekanbaru with quasi-experimental. There are two classes that will be sampled, namely the experimental and control classes with purposive sampling as a data collection technique. The data collection method used is a test with descriptive and inferential statistical data analysis techniques. Descriptive statistical analysis technique was used to describe the power obtained from the measurement results of the dependent variable, namely learning outcomes, inferential statistical analysis techniques were used to analyze sample data (pre-test and post-test). The results of descriptive statistical analysis showed that the average pre-test for the experimental and control classes were 50.10 and 54.31, while the post-test averages for the experimental and control classes were 76.79 and 68.13. In this study, the data were normally distributed, with a homogeneity value of 0.752 and when tested t the result was 0.002 < 0.05, so it can be concluded that there is an effect of realistic mathematics approach on student learning outcomes.The purpose of this study was to determine the effect of Realistic Mathematics Approach on the learning outcomes of seventh grade students of Junior High School 6 Pekanbaru with quasi-experimental. There are two classes that will be sampled, namely the experimental and control classes with purposive sampling as a data collection technique. The data collection method used is a test with descriptive and inferential statistical data analysis techniques. Descriptive statistical analysis technique was used to describe the power obtained from the measurement results of the dependent variable, namely learning outcomes, inferential statistical analysis techniques were used to analyze sample data (pre-test and post-test). The results of descriptive statistical analysis showed that the average pre-test for the experimental and control classes were 50.10 and 54.31, while the post-test averages for the experimental and control classes were 76.79 and 68.13. In this study, the data were normally distributed, with a homogeneity value of 0.752 and when tested t the result was 0.002 < 0.05, so it can be concluded that there is an effect of realistic mathematics approach on student learning outcomes.